Pentahelix's Collaboration In The Development of Halal Tourism For Sustainable Regional Economic Development - Santoso, Lukman; Tri Cahyani, Yutisa (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2022)
This paper aims to explore the implementation of the pentahelix collaboration policy in the development of halal tourism in the region, as well as to design an ideal synergy model for the development of sustainable halal tourism. They use the qualitative methodology and a comparative approach to two halal tourism development areas, Malang city and Banyuwangi regency. This research discovered comparative advantages to implementing the penta-helix collaboration policy in establishing halal tourism in the two locations where there are variances and diversity in implementing the pentahelix collaboration in halal tourism. Each region has advantages that multi-sector and multi-stakeholder institutions complement. The development of halal tourism in Malang and Banyuwangi is further stymied by the absence of rules as a legal framework for development. However, the two regions are working to assure and expedite the development of halal tourism following local wisdom. This research helps to fill gaps in the development of halal tourism in Malang and Banyuwangi. Furthermore, this research contributes to the region's role as a paradigm for developing sustainable halal tourism.